Recent efforts toward the development of peptide secondary structure mimetics at Molecumetics Ltd. for the discoveries of new drug candidates utilizing combinatorial chemistry with solid phase synthesis are described - Sharon, J.; Sarantopoulos, S.; den, W.; Kao, C.Y.; Baecher-Allan, C.M.; Santora, K.E.; Sompuram, S.R.; Petersen-Mahrt, S.; Williams, B.R. (Combinatorial Chemistry & High Throughput Screening, 2000)
We describe a technology for generating recombinant polyclonal antibody libraries (PCALs) that enables the creation and perpetuation of standardized mixtures of polyclonal whole antibodies specific for a multiantigen (or polyantigen). Therefore, this technology combines the advantages of targeting multiple antigenic determinants – high avidity, low likelihood of antigen escape variants, and efficient mediation of effector functions, with the advantages of using monoclonal antibodies – unlimited supply of standardized reagents and the availability of the genetic material for desired manipulations. The technology for generating recombinant polyclonal antibody libraries begins with the creation of phage display Fab (antibody) libraries. This is followed by selection of sublibraries with desired antigen specificities, and mass transfer of the variable region gene pairs of the selected sublibraries to a mammalian expression vector for generation of libraries of polyclonal whole antibodies. We review here our experiments for selection of phage display antibody libraries against microbes and tumor cells, as well as the recent literature on the selection of phage display antibody libraries to multiantigen targets.
Keywords: Recombinant polyclonal antibody libraries